The Adjustment to Online Learning of Chinese Exchange Students In the New Normal Era: A Case Study at Huachiew Chalermprakiet University - Thamvaja, Wilai (Academic and Research Journal of Liberal Arts (Online), 2024)
This research aims to study the learning problems, method of adjustment, and online learning adjustment process among Chinese exchange students. Mixed methods research was employed to achieve these objectives. The sample consisted of 65 Chinese exchange students in the batch 15th studying in the Bachelor of Arts program in communicative Thai as a second language program. Questionnaires and interviews were used to collect data. The statistics used were the mean, standard deviation, percentage, frequency value, and Pearson Product Moment Coefficient. The results of this study revealed that: 1) problems with online learning among Chinese exchange students ranged from most common problems to least common. The most common problem was communication problems, followed by attitude and behavioral problems, learning methods problems, environmental problems, curriculum and teaching problems, social and cultural problems, and technological problems, respectively. 2) the method of adjustment is found that most students adapt to struggle (48.40%) followed by a compromise reaction (47.84%), and withdrawal reaction (3.76%), respectively. 3) the adjustment process can be divided into 4 phases according to the U-Curve Model, including the honeymoon period, coping period, adjustment period, and post-adjustment period which looks like it spins around many times. Besides, some students do not have a honeymoon period. However, there is a culture shock and it leads to a frustration stage. So effective online learning requires collaboration between instructors, students, in terms of curriculum, and universities.